Cultural weed management practices shorten the critical weed-free period for soybean grown in the Northern Great Plains. Issue 1 (December 2019) - Rosset, Jonathan D.; Gulden, Robert H.
Abstract: Soybean [ Glycine max (L.) Merr.] has recently become a popular rotational crop in the Canadian Northern Great Plains where herbicide-resistant (HR) soybean cultivars have been widely adopted. Intense reliance on herbicides has contributed to the development of HR weeds in soybean and other crops. Cultural weed management practices reduce the need for herbicides and lower the selection pressure for HR weed biotypes by improving the competitiveness of the crop. The effects of two row spacings, three target densities, and three cultivars on the critical weed-free period (CWFP) in soybean were evaluated as three separate experiments in southern Manitoba. In the row-spacing experiment, soybean grown in narrow rows shortened the CWFP by up to three soybean developmental stages at site-years with increased weed pressure. In the target density experiment, low-density soybean stands lengthened the CWFP by one soybean developmental stage compared with higher-density soybean stands. The effect of soybean cultivar varied among locations, yet tended to be consistent within location over the 2-yr study, suggesting that competitive ability in these soybean cultivars was linked to edaphic and/or environmental factors. Generally, the cultivar with the shortest days to maturity, which also had the shortest stature, consistently had a longer CWFP. Each of these cultural practices were effective at reducing the need for in-crop herbicide applications.